Pengaruh Reward dan Punishment terhadap Kinerja Karyawan dengan Motivasi Kerja sebagai Variabel Intervening di Badan Usaha Milik Negara (Studi Kasus: PT. Semen Baturaja, Tbk) - Ilham Sidik; Hasmawaty AR; Muji Gunarto; Sulaiman Helmi (J-MAS (Jurnal Manajemen dan Sains), 2023)
The purpose of this study was to determine the effect of reward and punishment on performance with work motivation as an intervening variable.The variables in the study consisted of 2 independent variables, namely reward and punishment, 1 dependent variable, namely performance, and 1 intervening variable, namely motivation.The number of samples in this study were 91 respondents who are permanent employees of PT Semen Baturaja (Persero) Tbk.Determination of the number of samples using the slovin formula.Data obtained by distributing questionnaires using a Likert scale.Data processing uses Structural Equation Modeling analysis with SmartPLS.The data analysis technique consists of the Outer Model test and the Inner Model test.The results of the study show that 1) Reward has a significant and positive effect on performance.2) Reward has a significant and positive effect on motivation.3) Punishment has no significant and negative effect on performance.4) Punishment has a significant and positive effect on motivation.5) Motivation has a positive and significant effect on performance 6) Motivation is able to mediate rewards on performance 7) Motivation is able to mediate punishment on performance.